the effect of adding different levels of sugar beet molasses on some physical properties of the soil and on the productivity of potato plants - كردي, علا; جهاد إبراهيم ,; ربيع زينة,; نصر شيخ سليمان , (Latakia University Journal -Biological Sciences Series, 2024)
The cultivation was carried out during the first agricultural season in the year 2021 at the Scientific Research Station - Stekhris region, and it was followed in its completely randomized design. The experiment included four treatments of sugar beet molasses (B0=0-B1=75- B2=150-B3=225 l/ha). It was found that the bulk density of the soil decreased with the addition of molasses in the surface layer from 0-20 cm by 0.13 g/cm3 at the addition level of 225 liters/ha, while in the depth from 20-40 cm, the decrease was 0.23 g/cm3 compared to the control. It was found that the leaf surface area ranged from 3450 cm2 to 11606 cm2 per plant three months after planting, and the best area was at the level of adding 225 liters/ha of molasses. The productivity of one plant was highest when adding 225 liters/ha of molasses, reaching 3229 kg/dunum.